Breaking Down Barriers And Enhancing Communication Skills in Nursing - Tiara Amalia Mentari (UNIVERSITAS MUHAMMADIYAH SURABAYA, 2024)
Objective: Communication is an integral part of nursing skills. Comprehensive knowledge in this area is highly essential for a nurse. This research aims to explore nursing communication skills, barriers, and resolution strategies Methods: Literature review design. Using the PICO approach with specific keywords. Thirty-six journals were identified from online databases such as PubMed, Google Scholar, Scopus, and ScienceDirect, covering both English and Indonesian language studies, including quantitative, qualitative, literature, and scoping reviews. Results: The findings of this research illustrate that effective communication encounters several obstacles, such as understaffing, heavy workloads, language and cultural disparities, hierarchical systems, insufficient training, and physical or psychological challenges. Proposed solutions for effective communication encompass understanding patient requirements, highlighting empathy, nurturing adaptability and patience, being responsive, ongoing learning and employing communication models, tackling cross-cultural concerns, utilizing technology, and advocating for interdisciplinary collaboration to ensure comprehensive patient care and smooth information exchange among healthcare professionals. Conclusion: Implementation of these solutions aims to enhance nursing communication quality.